HtrA1 sensitizes ovarian cancer cells to cisplatin-induced cytotoxicity by targeting XIAP for degradation - He, Xiaoping (2011)
HtrA1, a member of serine protease family, has been previously found to be involved in resistance to chemotherapy in ovarian cancer although the underlying mechanism is not clear. Using mixture-based oriented peptide library approach, we previously identified X-linked inhibitor of apoptosis protein (XIAP), a member of the inhibitor of apoptosis proteins (IAPs) family as a potential substrate of HtrA1. The aim of this work is to investigate the link between HtrA1 and XIAP proteins and their relationships with chemoresistance in ovarian cancer. Our results showed that recombinant XIAP was degraded by purified wild type HtrA1 but not mutant HtrA1 in vitro. Consistent with the in vitro data, co-immunoprecipitation assays showed that HtrA1 and XIAP formed a protein complex in vivo. Ectopic expression of HtrA1 led to decreased level of XIAP in OV167 and OV202 ovarian cancer cells, while knockdown of HtrA1 resulted in increased level of XIAP in SKOV3 ovarian cancer cells. Furthermore, over-expression of HtrA1 in OV202 cells promoted cell sensitivity to cisplatin-induced apoptosis which could be reversed by increased expression of XIAP. The cleavage of XIAP induced by HtrA1 was enhanced by cisplatin treatment. Taken together, our experiments have identified XIAP as a novel substrate of HtrA1 and the degradation of XIAP by HtrA1 contributes to cell response to chemotherapy, suggesting that restoring the expression of HtrA1 may be a promising treatment strategy for ovarian cancer.